Generating finite state machine from WSMO choreography for testing Web services - Rusli, H. M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Web services composition is the act of combining several Web services in order to create a new service. The composition process includes planning service sequence, discovering services, selecting services and executing the plan. During service selection, it is important that the selected service not only meets the functionality of the required tasks, the selected service must also match the behavior of its client. This paper proposes an approach to test the interaction or choreography of the Web service by leveraging on transition rules that represent the behavior of the services. A Finite State Machine representation of the choreography is extracted using elements of the choreography. Test cases are then generated based on the Finite State Machine model using existing test generation approach.